2014
DOI: 10.1097/igc.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic Cancer InterGroup (GCIG) Consensus Review: Uterine and Ovarian Leiomyosarcomas

Abstract: Objective The GCIG aimed to provide an overview of uterine and ovarian leiomyosarcoma management. Methods Published articles and author experience were used to draft management overview. The draft manuscript was circulated to international members of the GCIG for review and comment, and appropriate revisions were made. Results The approach to management of uterine and ovarian leiomyosarcoma management is reviewed. Conclusions Uterine and ovarian leiomyosarcomas are rare, aggressive cancers that require s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…For patients with disease limited to the uterus or those with disease that seems to be completely resectable, hysterectomy with complete tumor debulking should be the initial goal of care. 12 In our study, complete cytoreduction was associated with improved PFS, which is consistent with findings by Leitao et al 6 However, we also found that cytoreduction to no residual disease was also associated with improved OS. Thus, surgery should be undertaken with the goal of no residual disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For patients with disease limited to the uterus or those with disease that seems to be completely resectable, hysterectomy with complete tumor debulking should be the initial goal of care. 12 In our study, complete cytoreduction was associated with improved PFS, which is consistent with findings by Leitao et al 6 However, we also found that cytoreduction to no residual disease was also associated with improved OS. Thus, surgery should be undertaken with the goal of no residual disease.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, our findings also support the notion that the role of surgery is much more limited in patients who present with widely metastatic and unresectable disease, unless the procedure is being performed for palliation. 12 Beyond the initial surgery, the current prospective data are insufficient to guide management recommendations for either uterus-limited disease or locally advanced, completely resected uLMS. A randomized trial looking at adjuvant pelvic radiation versus observation in patients with uterine-limited disease failed to demonstrate any difference in survival or recurrence rates in the radiation arm, 13 thus suggesting that radiation may have a limited role in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Tangjitgamol et al 41 concluded that lymph node size was not a good predictor of lymph node metastases in uterine cancer, removing the enlarged lymph nodes in uLMS was considerable. 42 Pelvic and/or paraaortic lymph node dissection was not routinely recommended by most authors since retroperitoneal involvement was found to be rare in their sample. 11 The low incidence of lymph node metastasis is similar to those women with uLMS of other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ULMS and ESS can show LG and high grade features, a factor that can play a role in histological diagnosis, but is not necessarily used for classification 6 8 9. Distinguishing ESS from ULMS, as well as LG tumours and LM from LG uterine sarcomas (ESS and ULMS), is usually straightforward, particularly on a hysterectomy specimen.…”
Section: Discussionmentioning
confidence: 99%